Association between sociodemographic factors and mental health status among secondary school students in Cambodia: a cross-sectional study using SDQ - Sophealeaksmy Em; Keisuke Teramoto; Kohei Yamada; Chansean Mam (International Journal of Public Health Science (IJPHS), 2026)
Adolescent mental health significantly influences social well-being and academic achievement, yet empirical data remains scarce in Cambodia. This study examined the association between sociodemographic characteristics and mental health status among Cambodian secondary school students using the Strengths and Difficulties Questionnaire (SDQ). A cross-sectional survey was conducted from March to April 2024 across five major provinces and Phnom Penh. Using purposive sampling, 1,528 students from urban and rural schools were recruited. Abnormal mental health was reported by 50.56% of females and 52.33% of students whose mothers had only elementary education. T-test and ANOVA analyses revealed significant associations between mental health and gender, school location, school type, and maternal education (p < 0.001), while socioeconomic status showed no significant impact. Findings emphasize that gender and maternal education are primary correlates of psychological well-being. These results necessitate gender-responsive school health programs and decentralized mental health services in rural areas. Furthermore, community initiatives should prioritize maternal health literacy to empower mothers as central caregivers, fostering supportive home environments for student resilience.